Wood anatomy of Fagus grandifolia subsp. mexicana (Fagaceae), endemic species from Mexico - Cuapio Hernández, Liliana; Borja-de la Rosa, Ma. Amparo; Reyes Trejo, Benito; Villanueva Morales, Antonio; Machuca Velasco, Roberto; Corona Ambriz, Alejandro (Instituto de Ecología, A.C., 2022)
Background and Aims: Fagus grandifolia subsp. mexicana inhabits Mexico, forming relict in the cloud forests of the Sierra Madre Oriental; it is an endemic taxon that is currently in danger of extinction. The aim of this study was to describe the macroscopic and microscopic anatomical features of the wood of F. grandifolia subsp. mexicana to contribute to its anatomical knowledge.Methods: The wood samples were obtained by a non-destructive method consisting of the extraction of cores from the stem of live trees and pieces of the trunk of one tree that recently had been felled by the wind. The anatomical description of the wood was made in the tangential, across, and radial planes, at the macroscopic level with wooden boards (7×12×1 cm section and polished) and microscopically with fixed slides of core sections. The anatomic description was made following the terminology by the International Association of Wood Anatomists. The Vulnerability index (VI), vessel grouping index (VIg), and mesomorphic index (MI) were also estimated. The RStudio program was used to perform the statistical tests and Excel to estimate the index.Key results: The wood of Fagus grandifolia subsp. mexicana is light brown colored, medium to high gloss, veining pronounced, straight grained and coarse texture, with diffuse porosity, simple and scalariform perforation plates (with 5-20 bars), opposite intervascular pits, tylosis, vasicentric tracheids, libiform fibers, apotracheal axial parenchyma diffuse and apotracheal parenchyma, heterogeneous rays, ray width uniseriate, biseriate, multiseriate and aggregate rays, prismatic crystals and silica bodies. Some anatomical features coincide with those of other species of the same genus.Conclusions: The description of the wood anatomy of F. grandifolia subsp. mexicana is the first for this taxon. Furthermore, it contributes to interrelating the information on its characteristics with that of other Fagus species of economic importance.